2015
DOI: 10.1001/jama.2015.10078
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnostic Yield of Chromosomal Microarray Analysis and Whole-Exome Sequencing in Children With Autism Spectrum Disorder

Abstract: Among a heterogeneous sample of children with ASD, the molecular diagnostic yields of CMA and WES were comparable, and the combined molecular diagnostic yield was higher in children with more complex morphological phenotypes in comparison with the children in the essential category. If replicated in additional populations, these findings may inform appropriate selection of molecular diagnostic testing for children affected by ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
322
3
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(379 citation statements)
references
References 48 publications
37
322
3
3
Order By: Relevance
“…Lenroot and Yeung (2013) reported that the majority of individuals diagnosed with ASD had typical brain and head size. However, in other studies, approximately 10 to 24 % of individuals diagnosed with ASD had persisting macrocephaly (Gillberg and de Souza 2002;Lainhart 2015;Nebel et al 2015;Sacco et al 2015;Tammimies et al 2015). In addition, a number of studies have reported that 3 to 15 % of individuals with ASD had persisting microcephaly (Gillberg and de Souza 2002;Nebel et al 2015;Roullet et al 2013;Stevens et al 2013).…”
Section: Does Asd Have Neurobiological Validity?mentioning
confidence: 94%
See 1 more Smart Citation
“…Lenroot and Yeung (2013) reported that the majority of individuals diagnosed with ASD had typical brain and head size. However, in other studies, approximately 10 to 24 % of individuals diagnosed with ASD had persisting macrocephaly (Gillberg and de Souza 2002;Lainhart 2015;Nebel et al 2015;Sacco et al 2015;Tammimies et al 2015). In addition, a number of studies have reported that 3 to 15 % of individuals with ASD had persisting microcephaly (Gillberg and de Souza 2002;Nebel et al 2015;Roullet et al 2013;Stevens et al 2013).…”
Section: Does Asd Have Neurobiological Validity?mentioning
confidence: 94%
“…In a meta-analysis, Sacco et al (2015) found only 5.7 % of individuals with ASD had macrocephaly and just 9.1 % had brain overgrowth. Tammimies et al (2015) also found that only 63 of 258 children with ASD had macrocephaly. Also countering the ASD early brain overgrowth model, 3 to 15 % of individuals diagnosed with ASD have been born with microcephalic brains (Nebel et al 2015;Roullet et al 2013;Stevens et al 2013).…”
Section: Does Asd Have Neurobiological Validity?mentioning
confidence: 95%
“…Nitric oxide, critical for blood flow regulation, is involved in the immune response and is believed to be a novel neurotransmitter. Production of the monoamine neurotransmitters dopamine, serotonin and norepinephrine as well as the circadian regulator melatonin, all require BH 4 . Interestingly, abnormalities in all of these pathways have been associated with ASD [23].…”
Section: Folate One Of the Body's Most Important Vitaminsmentioning
confidence: 99%
“…A notion of a pure genetic etiology is tempered by the fact that single gene and chromosomal defects are found in a minority of ASD cases, accounting for only 15.8% of cases when both chromosomal microarray and whole exome sequencing were used in one recent large study [4]. ASD has also been associated with exposures to numerous environmental agents during the prenatal and postnatal period [5].…”
mentioning
confidence: 99%
“…The diagnostic yield of known ASD patients through CMA is found to be 15-20% in most studies, as well as almost 30% by prior screening on complex cases of ASD [6]. In this procedure, a blood sample is taken from the patient, and the genetic material is then comprehensively scanned in comparison to a healthy genome control [10,11]. In identifying distinct variants from the control, this reveals mutations that may be related to the development of ASD in the patient [9].…”
Section: Introductionmentioning
confidence: 99%